South–South cohesiveness versus South–South rhetoric: Brazil and Africa at the UN General Assembly - Seabra, P.; Sanches, E. R. (International Politics, 2019)
South–South relations have regained widespread interest in recent years, together with increasingly visible stances on international stages. Brazil’s interactions with the African continent, in particular, came to epitomise such a perception while sustaining an expectation of mutual alignment in several global issues. However, these assumptions still lack empirical corroboration. Drawing on United Nations General Assembly voting data for the 1991–2013 timeframe, this article questions a supposed South–South solidarity at the multilateral institution with the largest global representation and identifies key thematic axes that incite greater collective stances. The analysis further sheds light on whether or not a common South–South agenda has emerged over time.